Activity of the Tyumen Commodity Exchange (1910–1917) - L. V. Merkulova (Омский научный вестник: Серия "Общество. История. Современность", 2024)
The article analyzes the factors and reasons that influenced the opening of the commodity exchange in Tyumen, as well as its activities in the period from 1910 to 1917. Based on the study of press materials and unpublished sources from the funds of the State Archive of the Tyumen region and the application of historical methods such as historical-comparative, historical-genetic, statistical, the aim of the study is achieved — the mechanism of the exchange is analyzed, the main directions of its activities are identified, its efficiency is assessed.